THE MOST IMPORTANT HUMAN ORIGINS STUDIES OF VIETNAM (1906 - 2018) - Nguyễn Lân Cường (Tạp chí Khoa học Đại học Đà Lạt)
This article summarizes all important research achievements concerning ancient human remains in Vietnam for over 100 years.In the Early Palaeolithic, more than half a million years ago, Homo erectus existed - this is the beginning of Vietnamese prehistory. Human evolution in Vietnam has taken place continuously from Homo erectus to Homo sapiens to Homo sapiens sapiens. The above data also enable us to realize the early and continuous sapienization in Vietnam. Early Homo erectus remains were found in Tham Khuyen and Tham Hai caves from more than half a million years ago. Late Homo sapiens remains were found in Lang Trang cave (80,000BP), in Hang Hum and Tham Om caves (60,000BP), and Ma Uoi cave (49,000BP). Homo sapiens sapiens remains were found at the Nham Duong, Thung Lang, and Keo Leng sites (40,000BP). The Son Vi inhabitants lived from 30,000 to 11,000BP and from the process of mixture became modern people. The paper presents the systemization and updated research on ancient human remains. From the data, we will better understand the process of formation and evolution of the human communities in the territory of Vietnam.